Progress in design of halloysite nanotubes-polymer nanocomposite membranes and their applications - Lijuan Qin; Guanying Dong; Yi Nie; Rawil Fakhrullin; Bing Zhang; Yatao Zhang (Advanced Membranes)
Driven by the diverse functionalization of halloysite nanotubes (HNTs) and advanced membrane preparation technologies, a tremendous progress in HNTs-polymer nanocomposite membranes has been made during the last dozen years. Yet even with these achievements, an elaborate and comprehensive overview on the rational design of HNTs-polymer nanocomposite membranes, their various application areas as well as the corresponding membrane performance status is still missing. Herein, we provide a timeline of the ongoing research on the advanced HNTs-polymer nanocomposite membranes and then outline the progress on: (1) versatile functionalization methods of the HNTs for the state-of-the-art HNTs-polymer nanocomposite membranes. (2) key routes to prepare and design the HNTs-polymer nanocomposite membranes, and the corresponding influences of the modified HNTs on their membrane structures and performances. (3) the overall inductive performances for specific applications in the areas of water treatment, gas treatment, energy conversion, as well as biomedicine. We envision that an insightful perspective will be timely presented in this review to stimulate the innovation in developing more advanced HNTs-polymer nanocomposite membranes, and then motivating and extending their applications.